Cytoprotective signaling by activated protein C requires protease-activated receptor-3 in podocytes - Madhusudhan, Thati; Wang, Hongjie; Straub, Beate K; Gröne, Elisabeth; Zhou, Qianxing; Shahzad, Khurrum; Müller-Krebs, Sandra; Schwenger, Vedat; Gerlitz, Bruce; Grinnell, Brian W; Griffin, John H; Reiser, Jochen; et al. (Blood, 2012)
The cytoprotective effects of activated protein C (aPC) are well established. In contrast, the receptors and signaling mechanism through which aPC conveys cytoprotection in various cell types remain incompletely defined. Thus, within the renal glomeruli, aPC preserves endothelial cells via a protease-activated receptor-1 (PAR-1) and endothelial protein C receptor-dependent mechanism. Conversely, the signaling mechanism through which aPC protects podocytes remains unknown. While exploring the latter, we identified a novel aPC/PAR-dependent cytoprotective signaling mechanism. In podocytes, aPC inhibits apoptosis through proteolytic activation of PAR-3 independent of endothelial protein C receptor. PAR-3 is not signaling competent itself as it requires aPC-induced heterodimerization with PAR-2 (human podocytes) or PAR-1 (mouse podocytes). This cytoprotective signaling mechanism depends on caveolin-1 dephosphorylation. In vivo aPC protects against lipopolysaccharide-induced podocyte injury and proteinuria. Genetic deletion of PAR-3 impairs the nephroprotective effect of aPC, demonstrating the crucial role of PAR-3 for aPC-dependent podocyte protection. This novel, aPC-mediated interaction of PARs demonstrates the plasticity and cell-specificity of cytoprotective aPC signaling. The evidence of specific, dynamic signaling complexes underlying aPC-mediated cytoprotection may allow the design of cell type specific targeted therapies.